ANALISIS KEBIJAKAN FISKAL KHULAFAUR RASYIDIN DAN RELEVANSINYA TERHADAP SISTEM FISKAL INDONESIA KONTEMPORER - Ahmad Saiful Anam; Sarpini Sarpini (CV. Denasya Smart Publisher, 2026)
This study examines fiscal policies during the era of the Khulafaur Rasyidin while assessing their relevance to Indonesia’s current fiscal system. It employs a qualitative method using a library research approach to collect and analyze data from various sources, including Islamic historical literature, Islamic economics books, academic journals, and regulations related to Indonesia’s fiscal system. The findings reveal that several aspects of fiscal policy during the Khulafaur Rasyidin era, such as effective zakat management, the prohibition of usury (riba), and an emphasis on public investment for societal welfare, have strong relevance to the fiscal challenges currently faced by Indonesia. Therefore, this study recommends the adoption of Islamic fiscal principles in the formulation of national fiscal policies to support sustainable and inclusive development. Additionally, the results of this research are expected to provide new insights for policymakers, academics, and economic practitioners in designing a more just, efficient, and equitable fiscal system.